Chiral Perovskite Nanoplatelets Exhibiting Circularly Polarized Luminescence through Ligand Optimization. Issue 19 (14th July 2022) - Hubley, Austin; Bensalah‐Ledoux, Amina; Baguenard, Bruno; Guy, Stephan; Abécassis, Benjamin; Mahler, Benoit
Abstract: Chiral halide perovskite nanocrystals have many applications in next‐generation optoelectronic devices due to their interaction with polarized light. Through careful selection of chiral organic surface ligands, control over the circular dichroism (CD) and circularly polarized luminescence (CPL) of these materials can be achieved. However, while recent developments of CD‐active perovskites have seen significant advances, effective CPL remains a challenge. Here, colloidal perovskite nanoplatelets are synthesized exhibiting room temperature CPL with dissymmetry factors up to g lum  = 4.3 × 10 −3 and g abs  = 8.4 × 10 −3 . Methylammonium lead bromide nanoplatelets are synthesized with a mixture of chiral dimethylbenzylammonium ligands and achiral octylammonium ligands, the precise ratio of which is shown to be critical to achieving high g ‐factors. The competitive binding of these surface ligands is investigated using 1 H NMR, and an equilibrium model is used to demonstrate the ligand affinity. The magnitude of CPL and CD is quantitatively shown to exhibit a linear correlation, such that g lum  = 0.40 × g abs . Last, by screening several amines with close structures, it is shown that subtle differences in ligand structure have significant impact on the resulting nanoplatelets CD signal. These findings provide new insights for the effective design of perovskites exhibiting CPL and facilitate the development of high‐performance devices based on circularly polarized luminescence. Abstract : Colloidal perovskite nanoplatelets are prepared exhibiting large magnitudes of circularly polarized luminescence and circular dichroism. The relationship is investigated between the surface ligands and the polarized absorption and emission of the chiral nanocrystals, providing insights for the development of high‐performance materials based on circularly polarized luminescence.